Peran kaum wanita dalam perjuangan kemerdekaan indonesia - amatullah, aliifah; Sari, Vina Nurmala; Muflikhon, Afidatil; Dzakiyyah, Fahimah (Maliki Interdisciplinary Journal, 2025)
The important role played by women in fighting for Indonesian independence during the colonial period, the independence struggle period, and the period after independence. Women did not participate in the battle for independence but participated directly in the armed resistance and underground movement. Apart from providing logistical support and setting up soup kitchens, women actively participated in the underground movement and armed resistance. Women’s courage is symbolized by figures such as Admiral Malahayati, Martha Christina Tiahahu, and Cut Nyak Dien. Malahayati represents women’s courage in the face of colonialism. However, women faced a number of difficulties and obstacles in carrying out their duties, including gender discrimination, difficulties and obstacles including discrimination based on sex, limited access to military and educational opportunities, in addition to societal expectations that limited women’s space for movement. Through participation in national development, socio-political organizations, and advocacy for women’s rights, women’s struggles continued after independence. They fought for gender equality in various fields of life with an emancipatory spirit.